Leadership styles’ effect on Oman food companies: mediating and moderating factors in performance - Maqbali, Rashid Al; Khudari, Mohamed (Edelweiss Applied Science and Technology, 2024)
The purpose of this research is to analyze how different types of leadership impact productivity in the Omani food business. In this case, we adopt a mixed-methods strategy, combining quantitative data from surveys given to 300 professionals with qualitative findings gleaned from in-depth interviews. The statistical investigations undertaken in this study comprise regression analysis as a means to explore the relationships between different leadership styles and performance outcomes. This study uses a mixed-method approach to its research design, combining qualitative interviews and quantitative surveys with a total sample size of 300 people. The regression study shows a favorable connection (r=0.60, p0.001) between transformative leadership and productivity in the workplace. Both employee performance (=0.60) and organizational success (=0.55) are positively correlated with transformative leadership. Transactional leadership is associated with improvement in both metrics. The two types of leadership, autocratic and laissez-faire, are not significantly linked. When compared to transactional leadership, transformational leadership is seen as having a more significant impact on organizational outcomes. The importance of acknowledgment and innovation is highlighted, and a fuller picture of leadership dynamics is shown, thanks to qualitative research. Practitioners can use the book as a guide to adopting a well-rounded approach to leadership in the dynamic environment of the Omani food industry. Despite its limitations, this study adds important depth to the discussion of what makes for good leadership. These results provide valuable insights that could guide future research and strategic planning efforts.